2013
DOI: 10.2174/1875397301206010055
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Dehalogenase-Based Protein Fusion Tag Capable of Rapid, Selective and Covalent Attachment to Customizable Ligands

Abstract: Our fundamental understanding of proteins and their biological significance has been enhanced by genetic fusion tags, as they provide a convenient method for introducing unique properties to proteins so that they can be examinedin isolation. Commonly used tags satisfy many of the requirements for applications relating to the detection and isolation of proteins from complex samples. However, their utility at low concentration becomes compromised if the binding affinity for a detection or capture reagent is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 80 publications
(85 reference statements)
4
117
1
Order By: Relevance
“…The Halo tag can be labeled efficiently and covalently by Halo ligands conjugated to a variety of organic fluorescent dyes for different imaging purposes (10). We purified recombinant dCas9 fusion protein expressed in Escherichia coli and labeled the protein with Halo ligands conjugated with Janelia Fluor 646 (JF646) (11).…”
Section: Resultsmentioning
confidence: 99%
“…The Halo tag can be labeled efficiently and covalently by Halo ligands conjugated to a variety of organic fluorescent dyes for different imaging purposes (10). We purified recombinant dCas9 fusion protein expressed in Escherichia coli and labeled the protein with Halo ligands conjugated with Janelia Fluor 646 (JF646) (11).…”
Section: Resultsmentioning
confidence: 99%
“…To increase its stability, 22 mutations have previously been introduced to create the more stable HaloTag7 protein for recombinant protein work 15; 16 . We hypothesized that these mutations would also provide increased stability in mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, mutagenesis of small single-chain enzymes has yielded variants that self-label covalently with a fluorophore substituent in the course of one catalytic turnover when provided with an appropriate cell-permeable, dye-derivatized substrate. This approach produced the so-called SNAP (Corrêa et al 2013), CLIP (Gautier et al 2008), and Halo (Encell et al 2012) tags. It is important to emphasize, however, that studies tracking hybrid proteins must be confirmed by independent approaches (e.g., genetic complementation) that show they retain biological function; sadly, such constructs are often used and conclusions drawn without this necessary validation.…”
Section: Seeing Is Believingmentioning
confidence: 99%